Urgensi Penerapan Sistem Identifikasi Sidik Jari Nasional dalam Penegakan Hukum di Indonesia - Provostian, David (Jurnal JURISTIC, 2024)
This study examines the urgency of implementing a national fingerprint identification system in law enforcement in Indonesia. The research problem is the lack of a comprehensive and integrated fingerprint database in Indonesia, hindering effective criminal investigation and identification. This study uses a normative juridical approach, analyzing relevant laws and regulations related to fingerprint identification and criminal justice systems. The study found that a national fingerprint identification system is crucial to improve the accuracy and efficiency of criminal investigations, prevent identity fraud, and enhance national security. The implementation of such a system will significantly benefit law enforcement agencies in identifying suspects, tracking criminals, and solving crimes.